A qualitative assessment of a gender-sensitive agricultural training program in Benin: Findings on program experience and women’s empowerment across key agricultural value chains - Eissler, Sarah; Diatta, Ampa Dogui; Heckert, Jessica; Nordehn, Caitlin (International Food Policy Research Institute, 2021)
This study presents qualitative findings from an assessment conducted by the International Food Research Institute and Cultural Practice, LLC of the African Union Development Agency-New Partnership for Africa’s Development (AUDA-NEPAD) Agricultural Technical Vocational Education and Training program for women (ATVET4Women) in Benin, supported by the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). ATVET4Women in Benin targets women working in value chains for four target commodities (soy, rice, chicken, and compost) to support capacity building in their respective nodes (production, processing, and marketing). The contributions of this study are multifold. First, it assesses program experiences and impacts. Second, it examines the gender dimensions of production, processing, and marketing activities in four specific value chains. Third, this research is a component of a broader study to adapt and validate the project-level Women’s Empowerment in Agriculture Index for market inclusion (pro-WEAI+MI) on key agricultural value chains in Benin and Malawi for ATVET4Women. This study employed multiple qualitative methods to assess beneficiaries’ program experiences and impacts. Fifteen key informant interviews were conducted with various actors along the value chain and agro-processing center managers involved in ATVET4Women. Thirty-eight semi-structured interviews were conducted with women beneficiaries of ATVET4Women, husbands of beneficiaries, women that were involved in the value chain but did not participate in ATVET4Women, and ATVET4Women trainers. Structured observations were conducted of five ATVET4Women training centers. In general, women beneficiaries and their husbands shared positive reviews of ATVET4Women in that the program increased women’s confidence in their abilities and taught women best practices for producing and selling higher quality products, generating higher incomes for women. Women noted several challenges and barriers to participate in ATVET4Women, including limited availability to travel to or partake in the trainings due to competing demands and priorities on their time, requiring their husbands’ permission to attend, and limited means to support travel to and from trainings. Related to findings around empowerment, results suggest that an empowered woman is closely tied to her ability to generate income, regardless of her decision-making autonomy, whereas an empowered man is one who generates higher incomes and is autonomous in his decision-making. A woman is expected to be submissive to her husband and defer to his decision-making, which holds implications for her ability to participate in activities outside of the household, including but not limited to ATVET4Women and similar programs. This study concludes with specific recommendations for ATVET4Women and similar programs to consider in future iterations of further programming to increase women’s empowerment in Benin.